Uncontrolled hypertension is associated with increased risk of graft failure in kidney transplant recipients: a nationwide population-based study - Kim, Chang Seong; Oh, Tae Ryom; Suh, Sang Heon; Choi, Hong Sang; Bae, Eun Hui; Ma, Seong Kwon; Jung, Jin Hyung; Kim, Bongseong; Han, Kyung-Do; Kim, Soo Wan (Frontiers in Cardiovascular Medicine, 2023)
Backgroud: Hypertension is highly prevalent in patients with kidney transplantation caused by transplantation-related immunologic or non-immunologic risk factors. However, whether a strict definition of hypertension (≥130/80 mmHg) and subdivided blood pressure (BP) groups are associated with an increased risk of graft failure after kidney transplantation using a nationwide large cohort study are still unknown. Methods: Using Korena National Health Insurance Service data, we included 14,249 patients who underwent kidney transplantation from 2002 to 2016. Patients were categorized into five BP groups according to the 2021 Kidney Disease: Improving Global Outcomes practice guidelines for BP management: normal BP (<120/80 mmHg), elevated BP (120–129/<80 mmHg), incident hypertension (≥130/80 mmHg), and controlled or uncontrolled hypertension with anti-hypertensive medications. Results: The primary outcome was graft failure, which occurred in 1,934 (13.6%) participants during the 6-year follow-up. After adjusting for covariates, hypertension was associated with a higher risk of graft failure [Adjusted hazard ratio (AHR), 1.70; 95% confidence interval (CI), 1.48–1.96)] than no-hypertension. The AHR for graft failure was the highest in patients with uncontrolled hypertension (AHR, 2.13; 95% CI, 1.80–2.52). The risk of graft failure had a linear relationship with systolic and diastolic BP, and pulse pressure. Conclusions: In this nationwide population-based study, hypertension ≥ 130/80 mmHg based on the 2021 KDIGO BP guidelines in kidney transplantion recipients, and elevated systolic and diastolic BP, and pulse pressure were associated with the risk of developing graft failure in kidney transplant recipients.